Influence of Azadirachta indica leaf extracts on tumor necrosis factor-α and interleukin-6 in albino rats and its computational analysis: Effect of A. indica leaf extracts on TNF-α and IL-6 in albino - Khadam, Aniza; Alyas, Sobia; Zahra, Naureen; Ahmad, Sohail; Sarwar, Abid; Khan, Ayaz Ali; Aziz, Tariq; Alharbi, Metab; Alasmari, Abdullah F. (Cellular and Molecular Biology, 2024)
The current study was designed to investigate the effect of A. indica (Neem) leaf extracts (ethanolic and aqueous) in yeast-induced pyrexia and acetic acid-induced writhing in rat models to evaluate the antipyretic and analgesic biomarkers and its phytochemical screening with computational analysis. For the antipyretic activity model 60 albino rats (160-200g) of either sex were divided into 4 groups and all groups were injected with yeast to induce pyrexia. Out of 4 groups, first group (control) consisted of 6 rats, treated with normal saline, the second group (standard) comprised 6 rats, treated with paracetamol. Third and fourth experimental groups consisted of 48 rats, treated with A. indica leaf ethanolic and aqueous extracts at doses of (50, 100, 200 and 400mg/kg b.w). For analgesic activity group division was the same and all groups were injected with acetic acid to induce pain TNF-α and IL-6 levels were measured using ELISA kits after blood samples were taken and serums were separated. An acute toxicity study was performed. In molecular docking, nimbandiol and nimbolide were used as ligand molecules to target protein Tnf-α and IL-6. In both activities at the dose of 400mg/kg, group III showed significant inhibition (p<0.05). Biomarkers showed significant results at the dose of 400mg/kg. Phytochemical screening was performed to reveal the existence of various active constituents. In molecular docking, nimbandiol and nimbolide showed -5 and -5.3 binding energies respectively, as compared to the standard drug paracetamol with -4.2 binding energy to TNF-Alpha protein. Therefore, A. indica extracts can be used as a valuable drug for the treatment of pain and fever.